Measurable properties of the standard Z0 in a SU(2)L* × SU(2)L × U(1)y scenario - Epele, Luis Nicolás (1991)
The low-energy limit of ourSU(2)L*×SU(2)L×U(1)Y electroweak model is analysed in order to fix the parameters. Bounds coming from the electron and muon magnetic anomaly are also considered. The resulting predictions for the standard Z-boson are presented. They are compatible with the recent SLC and LEP data.